Efektivitas Pelatihan Pemberian Makan Bayi Dan Anak (PMBA) Terhadap Pengetahuan dan Sikap Kader Posyandu di Kabupaten Lombok Timur - Laila Mardiana Rohmatillah; Nurwahidah; Aulia Alifariani (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
The Infant and Young Child Feeding (IYCF) Training is a strategic effort to enhance the knowledge and attitudes of community health workers (posyandu cadres) in providing nutritional counseling. This study aims to analyze differences in the knowledge and attitudes of posyandu cadres who have and have not received IYCF training in East Lombok Regency. Using a descriptive-analytical method with a posttest-only control design, the study involved two groups: cadres who had participated in the training and a control group who had not. The results revealed a significant increase in knowledge among cadres who had undergone the training compared to the control group (p < 0.05). Furthermore, the IYCF training contributed to a more positive attitude among cadres in delivering nutritional counseling, although its effect on motivation was relatively low. This study highlights the importance of IYCF training as an effective intervention to improve the quality of nutritional services, which is expected to support the reduction of malnutrition and stunting prevalence in the region. These findings can serve as a reference for developing continuous training programs for health workers in other areas.